Real‐world experience using hydroxyurea in children with sickle cell disease in Lilongwe, Malawi. Issue 11 (9th August 2019) - Mvalo, Tisungane; Topazian, Hillary M.; Kamthunzi, Portia; Chen, Jane S.; Kambalame, Isobel; Mafunga, Pilirani; Mumba, Noel; Chiume, Msandeni; Paseli, Khadija; Tegha, Gerald; Kumwenda, Wiza; Heimlich, J. Brett; et al.
Abstract: Introduction: Sickle cell disease (SCD) is among the most common inherited hematologic diseases in sub‐Saharan Africa (SSA). Historically, hydroxyurea administration in SSA has been restricted due to limited region‐specific evidence for safety and efficacy. Methods: We conducted a prospective observational cohort study of pediatric patients with SCD in Malawi. From January 2015 to November 2017, hydroxyurea at doses of 10–20 mg/kg/day was administered to children with clinically severe disease (targeted use policy). From December 2017 to July 2018, hydroxyurea was prescribed to all patients (universal use policy). Results: Of 187 patients with SCD, seven (3.7%) died and 23 (12.3%) were lost to follow‐up. The majority (135, 72.2%) were prescribed hydroxyurea, 59 (43.7%) under the targeted use policy and 76 (56.3%) under the universal use policy. There were no documented severe toxicities. Under the targeted use policy, children with SCD demonstrated absolute decreases in the rates of hospitalization (−4.1 per 1000 person‐days; −7.2, −1.0; P = .004), fevers (−4.2 per 1000 person‐days; −7.2, −1.1; P = .002), transfusions (−2.3 per 1000 person‐days; 95% confidence interval: −4.9, 0.3; P = .06), and annual school absenteeism (−51.2 per person‐year; −60.1, −42.3; P < .0001) within 6 months of hydroxyurea commencement. Conclusion: We successfully implemented universal administration of hydroxyurea to children with SCD at a tertiary hospital in Malawi. Similar to recently reported trials, hydroxyurea was safe and effective during routine programmatic experience, with clinical benefits particularly among high‐risk children. This highlights the importance of continued widespread scale‐up of hydroxyurea within SCD programs across SSA.